Transfer of Meropenem in the ex Vivo Human Placenta perfusion Model - Michael Hnat; Roger E. Bawdon (Hindawi Limited, 2005)
Objectives. To determine maternal-fetal transplacental passage of meropenem in the ex vivo human perfusion model.